Code-switching Habits in Group Discussions by Students of English as Foreign Language - Rahmawansyah Sahib; Andi Miftahul Maulidil Mursyid; Wira Kafryawan; Najiba Nawing (JELITA, 2021)
This study investigated the habit of code-switching by EFL students at Bulukumba Senior High School in English Group Discussion. It focused on exploring types of code-switching used by EFL students in English Group Discussion, and the dominant type of code-switching used by EFL students in English Group Discussion. The researchers applied mixed-method, which was a combination of qualitative and quantitative. This study took one class of EFL students as the research subject. The data was gathered through classroom recording by using a video recorder, interview, and field notes. The data analysis showed that students used five code-switching types, namely situational code-switching, metaphorical code-switching, intra-sentential code-switching, inter-sentential code-switching, and tag switching. The dominant type used by EFL students in English Group Discussion was inter-sentential in situational code-switching. In addition, the dominant type occurred in metaphorical code-switching was intra-sentential. The research result indicated that students used code-switching because it was needed in the classroom interaction like English Group Discussion.